Eutelsat HTS systems. (26th January 2016) - Fenech, H.; Tomatis, A.; Amos, S.; Soumpholphakdy, V.; Serrano Merino, J. L.
Summary: KA‐SAT is the first of the second generation of high throughput satellite (HTS) systems. Constructed by Airbus, it was launched in 2010. It delivers over 90 Gbps capacity over 82 spots in Ka‐band over Europe, North Africa and the Middle East. It represents a complete infrastructure with the ground segment complement so as to deliver a suite of services including Internet access, broadcasting and satellite news gathering. The KA‐SAT HTS system includes an integrated ground and satellite infrastructure: the ground infrastructure comprises a network of ten gateways that are connected to the main European point of presences, to the Internet backbone, to the network operations centre and a centralised operational control centre by Skylogic in Turin. Skylogic interfaces with all the customers. Besides the operational KA‐SAT, there are four other HTS systems launched or to be launched by Eutelsat: EUTELSAT 3B launched in April 2014, EUTELSAT 36C in 2015, EUTELSAT 65 West A in 2016 and EUTELSAT 172B in 2017. These systems represent a range of HTS systems for Eutelsat, which push the envelope of applications and provide the performance critical to operators. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : HTS systems are a breakthrough in satellite communications because they offer a considerable reduction in the service cost. This brings satellite communications closer to the consumer with costs and quality of service comparable with terrestrial services and on a ubiquitous basis.